It’s All About Timing: Early Feeding Promotes Intestinal Maturation by Shifting the Ratios of Specialized Epithelial Cells in Chicks - Reicher, Naama; Melkman-Zehavi, Tal; Dayan, Jonathan; Uni, Zehava (Frontiers in Physiology, 2020)
The small intestine (SI) of chicks (Gallus gallus) matures rapidly during the initial post-hatch period and acquires digestive, absorptive and secretive capabilities. The effects of the timing of first feeding on the quantities and distribution of specialized epithelial cells, which generate and maintain SI morphology and functionality, have not yet been examined. In this study, we identified specialized SI epithelial cell sub-types, including stem, progenitor, proliferating and differentiated cells within crypts and villi of chicks during the first 10d post-hatch, by in-situ hybridization, immunofluorescence and histochemical staining. We then examined their quantities and ratios between day of hatch and d10 in chicks that were fed upon hatch (early feeding, EF), compared to chicks that were fed 24h post-hatch (delayed feeding, DF). Results showed that EF increased total cell quantities in the crypts and villi at days 1, 3, 7 and 10, compared to DF (P<0.0001). At d3, EF, in comparison to DF, decreased crypt stem cell proportions (P<0.0001), increased crypt proliferating (P<0.01) and differentiated (P<0.05) cell proportions, and increased villus enterocyte proportions (P<0.01). By d10, EF increased both the quantities and proportions of villus enterocytes and goblet cells, compared to DF. We conclude that feeding upon hatch, compared to 24h-delayed feeding, enhanced SI maturation and functionality by increasing the quantities and proportions of proliferating and differentiated cells, thus expanding the digestive, absorptive and secretive cell populations throughout the initial post-hatch period.